Contribution of patient, physician, and environmental factors to demographic and health variation in colonoscopy follow‐up for abnormal colorectal cancer screening test results. Issue 18 (11th May 2017) - Partin, Melissa R.; Gravely, Amy A.; Burgess, James F.; Haggstrom, David A.; Lillie, Sarah E.; Nelson, David B.; Nugent, Sean M.; Shaukat, Aasma; Sultan, Shahnaz; Walter, Louise C.; Burgess, Diana J.
Abstract : BACKGROUND: Patient, physician, and environmental factors were identified, and the authors examined the contribution of these factors to demographic and health variation in colonoscopy follow‐up after a positive fecal occult blood test/fecal immunochemical test (FOBT/FIT) screening. METHODS: In total, 76, 243 FOBT/FIT‐positive patients were identified from 120 Veterans Health Administration (VHA) facilities between August 16, 2009 and March 20, 2011 and were followed for 6 months. Patient demographic (race/ethnicity, sex, age, marital status) and health characteristics (comorbidities), physician characteristics (training level, whether primary care provider) and behaviors (inappropriate FOBT/FIT screening), and environmental factors (geographic access, facility type) were identified from VHA administrative records. Patient behaviors (refusal, private sector colonoscopy use) were estimated with statistical text mining conducted on clinic notes, and follow‐up predictors and adjusted rates were estimated using hierarchical logistic regression. RESULTS: Roughly 50% of individuals completed a colonoscopy at a VHA facility within 6 months. Age and comorbidity score were negatively associated with follow‐up. Blacks were more likely to receive follow‐up than whites. Environmental factors attenuated but did not fully account for these differences. Patient behaviors (refusal, private sector colonoscopy use) and physician behaviors (inappropriate screening) fully accounted for the small reverse race disparity and attenuated variation by age and comorbidity score. Patient behaviors (refusal and private sector colonoscopy use) contributed more to variation in follow‐up rates than physician behaviors (inappropriate screening). CONCLUSIONS: In the VHA, blacks are more likely to receive colonoscopy follow‐up for positive FOBT/FIT results than whites, and follow‐up rates markedly decline with advancing age and comorbidity burden. Patient and physician behaviors explain race variation in follow‐up rates and contribute to variation by age and comorbidity burden. Cancer 2017;123:3502‐12 . Published 2017. This article is a US Government work and is in the public domain in the USA. Abstract : In the Veterans Health Administration, blacks are more likely to receive colonoscopy follow‐up for positive fecal occult blood test/fecal immunochemical test results than whites, and follow‐up rates decline with advancing age and comorbidity burden. Patient behaviors (refusal, private sector colonoscopy use) and physician behaviors (inappropriate screening) explain race variation in follow‐up rates and contribute to age and comorbidity variation.